2015
DOI: 10.1136/bcr-2015-209523
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial osseous metaplasia: an unusual cause of infertility

Abstract: SUMMARYOsseous metaplasia of the endometrium is a rare disorder associated with the presence of bone in the uterine endometrium. Most patients with this condition presenting with infertility do so owing to the presence of a foreign body in the endometrium. We report a case of a 38-year-old woman who presented with secondary infertility due to osseous metaplasia in the endometrial cavity. She conceived spontaneously after hysteroscopic removal of the bony fragments from the uterus. Uterine osseous metaplasia is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 7 publications
1
12
0
2
Order By: Relevance
“…Although its etiology still remains unclear, there are two theories regarding the pathophysiology of the disease including: fetal bone retention following an abortion later than three -month gestational weeks, and osseous metaplasia of endometrial stroma [1,2]. Inconsistent with the reported cases in the literature, our case had no abortus history.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Although its etiology still remains unclear, there are two theories regarding the pathophysiology of the disease including: fetal bone retention following an abortion later than three -month gestational weeks, and osseous metaplasia of endometrial stroma [1,2]. Inconsistent with the reported cases in the literature, our case had no abortus history.…”
Section: Discussionsupporting
confidence: 69%
“…It may be seen following late abortions. Its etiology is not clearly known; however, endometrial tissue osseous metaplasia or fetal bone retention are considered as the possible causes [1,2]. Herein, we report a case who was admitted to our clinic due to infertility and diagnosed and treated through hysteroscopy.…”
Section: Introductionmentioning
confidence: 96%
“…Most patients with this condition presenting with infertility do so owing to the presence of a foreign body in the endometrium [12]. Spontaneous conception and birth are likely to occur when the osseous metaplasia of the endometrium is treated by the removal of bone fragments [13].…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the patients are in the reproductive age group with history of first or second trimester abortion, either therapeutic or spontaneous and have normal menstrual cycle in the postabortive period as noted in our case. [1][2][3]8,9 The time interval between the antecedent abortion and discovery of endometrial ossification varies from 8 weeks to 14 years. Osseous endometrium is an endogenous non-neoplastic pathological condition as no tissue reaction is found in the endometrial tissue studied and the endometrium showed normal regular cyclical changes in response to ovarian hormones.…”
Section: Discussionmentioning
confidence: 99%